God's Maidservants: a Pentecostal Women (Counter)Narrative - Coral Gómez, L. Valentina (Filanderas, 2020)
By claiming that women and men can both hear God’s call and can both serve God in the same capacities, some Pentecostal and Neo-Pentecostal churches seem to give women a new sense of self-worth and empowerment. An analysis of the IDMJI, a Neo-Pentecostal Church established in Colombia, and its political party, MIRA, allowed me not only to appreciate how this process of empowerment works but also to observe how these religious groups, more often than not, keep intact several gender stereotypes that can be detrimental to their own parishioners and to society at large. The IDMJI is led by a woman who claims that both men and women can preach. Its political party have acted in the past on behalf of women and other minorities, asking for parity in public office and protesting against gender and domestic violence. Nevertheless, the value they give to women is still highly related to their role as wives and mothers, and they exclude the possibility of sexual or affective relations that do not conform to the heterosexual norm. Thus, they continue reinforcing patriarchal values and jeopardizing the self-determination of women as well as the rights of the members of the LGBTQ+ communities.
Keywords: Empowerment; Pentecostalism; Christianity; Women's Rights; LGBTQ Rights